Novel antibody–antibiotic conjugate eliminates intracellular S. aureus - Lehar, Sophie M.; Pillow, Thomas; Xu, Min; Staben, Leanna; Kajihara, Kimberly K.; Vandlen, Richard; DePalatis, Laura; Raab, Helga; Hazenbos, Wouter L.; Hiroshi Morisaki, J.; Kim, Janice; Park, Summer; et al. (Nature (London), 2015)
Staphylococcus aureus is considered to be an extracellular pathogen. However, survival of S. aureus within host cells may provide a reservoir relatively protected from antibiotics, thus enabling long-term colonization of the host and explaining clinical failures and relapses after antibiotic therapy. Here we confirm that intracellular reservoirs of S. aureus in mice comprise a virulent subset of bacteria that can establish infection even in the presence of vancomycin, and we introduce a novel therapeutic that effectively kills intracellular S. aureus. This antibody–antibiotic conjugate consists of an anti- S. aureus antibody conjugated to a highly efficacious antibiotic that is activated only after it is released in the proteolytic environment of the phagolysosome. The antibody–antibiotic conjugate is superior to vancomycin for treatment of bacteraemia and provides direct evidence that intracellular S. aureus represents an important component of invasive infections. Antibiotic-resistant strains of Staphylococcus aureus , such as MRSA, are proving increasingly difficult to treat; here, one reason for this is confirmed to be the fact that S. aureus bacteria can reside in intracellular reservoirs where they are protected from antibiotics, but a new strategy—based on an antibody–antibiotic conjugate—can specifically target these reservoirs. A new approach to targeting S. aureus Antibiotic-resistant strains of Staphylococcus aureus , such as methicillin-resistant S. aureus (MRSA), are proving increasingly difficult to treat. This study confirms that one reason for this is the ability of the pathogen to reside in intracellular reservoirs where they are protected from antibiotics. To counter this barrier, the authors develop a new strategy — based on an antibody–antibiotic conjugate (AAC) — to specifically target these reservoirs. The antibody binds to wall teichoic acids on the surface of S. aureus cells, and internalization of AAC-opsonized bacteria by host cells results in removal by host proteases of the linker between the antibody and the antibiotic, thereby releasing the antibiotic in its active form. A single dose of AAC is effective in a mouse model of bacteraemia, and is superior to the use of vancomycin, the current standard of care for MRSA infection. These findings are a proof-of-principle for the possibility of using antibody carriers to deliver existing antibiotics in a way that could ensure their continued clinical success.